The Implementation of the Direct Method Using Synonyms in Teaching Arabic Vocabulary: A Case Study - Nur Qomari; Apri Wardana Ritonga (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study investigates the implementation of the direct method through the use of synonyms in teaching Arabic vocabulary. Grounded in the theoretical framework of behaviorism, this research responds to ongoing challenges in delivering practical and effective Arabic vocabulary instruction to non-native learners. The primary objective was to examine how direct instruction and reinforcement strategies impact students’ comprehension and usage of Arabic vocabulary.Methodology: A qualitative descriptive methodology was employed, with data collected through semi structured interviews, classroom observations, and documentation. The participants consisted of Arabic language instructors and first-semester students enrolled in the university’s Arabic language program.Findings: The findings indicate that the direct method, when integrated with synonym-based vocabulary presentation, facilitates meaningful learning, especially when supported by creative instructional media, an immersive linguistic environment, and consistent reinforcement techniques. The active use of Arabic beyond the classroom setting, coupled with immediate corrective feedback from instructors, played a critical role in enhancing learners’ vocabulary retention and usage.Implications/Novel Contribution: This research contributed to language and instruction domains of research by providing policy directions. The involvement of native Arabic speakers further enriched students’ lexical acquisition, providing authentic exposure and modeling. These results underscore the pedagogical value of combining the direct method with contextual reinforcement in Arabic language instruction.